1960
DOI: 10.5962/bhl.title.7310
|View full text |Cite
|
Sign up to set email alerts
|

The biological role of ribonucleic acids

Abstract: Next to nothing was known a quarter of a century ago about the biological role and the intracellular localization of the nucleic acids. All that was well established was the existence of two different types of nucleic acids, which correspond to the deoxyribonucleic (DNA) and ribonucleic (RNA) acids of the present day. They were called, respectively, thymonucleic and zymonucleic acids, because purified preparations had only been obtained from thymus and yeast. It was erroneously believed that thymonucleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Robinson & Ware (1988) also found increasing RNA/DNA ratios even in standard herring larvae until the sac stage. It is known that the rapidly growing organisms apparently synthesize and accumulate RNA needed for protein synthesis (Brachet 1955; Bulow 1970). In the present investigation also, a positive correlation between the concentration of RNA, DNA and RNA/DNA ratios of the muscle and growth of the fish was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Robinson & Ware (1988) also found increasing RNA/DNA ratios even in standard herring larvae until the sac stage. It is known that the rapidly growing organisms apparently synthesize and accumulate RNA needed for protein synthesis (Brachet 1955; Bulow 1970). In the present investigation also, a positive correlation between the concentration of RNA, DNA and RNA/DNA ratios of the muscle and growth of the fish was observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the factor responsible for this phenomenon, has not been studied previously. The behaviour of EAT cells was studied by several investigators, both in a natural environment [3,10] and in an artificial environment [5,11,12]. It seems to be clear from these studies that by maintenance of these cells in vitro in isotonic solution, a gradual decrease in their vitality occurs, associated most probably with a modification of various metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the RNA content of cells and their activity in the synthesis of protein, as shown by the pioneering cytological work of Caspersson and of Brachet and their co-workers, was the first indication of the role of ribosomes in protein synthe-sis [see (29)]. In studies beginning in the 1930's it was shown that the RNA or ribosome content of cells correlated well with the rate of growth of animal and plant tissues, with the rate of protein synthesis in particular types of cells, and with the rate of division of microbes.…”
Section: Protein and Rna Synthesismentioning
confidence: 99%
“…Abundant evidence in the form of historical photographs and surveys and an historical site record maintained by the U.S. Forest Service clearly establishes the general stability of the structure and negates Ranse Im's claim-. 29. We are fortunate that at the present time the U.S. Forest Servise, Medicine Wheel District, and the Departmiient of Anthropology, University of WscmCiing, are studying the archeological basis of the strLcitLure.…”
mentioning
confidence: 99%